2022
DOI: 10.3390/jcm11071895
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Operating Room Nurse Preoperative Dialogue on Anxiety, Satisfaction and Early Postoperative Outcomes in Patients Undergoing Major Visceral Surgery—A Single Center, Open-Label, Randomized Controlled Trial

Abstract: Background: Anxiety is common before surgery and known to negatively impact recovery from surgery. The aim of this study was to evaluate the impact of a preoperative nurse dialogue on a patient’s anxiety, satisfaction and early postoperative outcomes. Method: This 1:1 randomized controlled trial compared patients undergoing major visceral surgery after a semistructured preoperative nurse dialogue (interventional group: IG) to a control group (CG) without nursing intervention prior to surgery. Anxiety was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Most studies apply the intervention in a single session, with an average duration of less than 30 min, anxiety is usually assessed with the State-Trait Anxiety Inventory (STAI), one of the most researched and widely used measures of general anxiety, which is also available in many different languages (Julian, 2011) and 5/emotional support throughout the process (Dias et al, 2022a(Dias et al, , 2022bNg et al, 2022;Ruiz-Hernández et al, 2021) In addition, nurses can work with other health care professionals to develop an individualised treatment plan that addresses specific patient needs (Turunen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies apply the intervention in a single session, with an average duration of less than 30 min, anxiety is usually assessed with the State-Trait Anxiety Inventory (STAI), one of the most researched and widely used measures of general anxiety, which is also available in many different languages (Julian, 2011) and 5/emotional support throughout the process (Dias et al, 2022a(Dias et al, , 2022bNg et al, 2022;Ruiz-Hernández et al, 2021) In addition, nurses can work with other health care professionals to develop an individualised treatment plan that addresses specific patient needs (Turunen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they have specific training in patient care and are trained to provide emotional care and support. Thus, nurses can use a variety of strategies and practices aimed at reducing preoperative anxiety and stress, helping patients feel more prepared and confident and improving their emotional well‐being including: 1/effective communication with patients, 2/education: about the procedure, potential complications, pain management and postoperative care, 3/implementing relaxation techniques, 4/creating a calm and relaxing environment both in the waiting room and in the patient's room and 5/emotional support throughout the process (Dias et al, 2022a, 2022b; Ng et al, 2022; Ruiz‐Hernández et al, 2021) In addition, nurses can work with other health care professionals to develop an individualised treatment plan that addresses specific patient needs (Turunen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Giusti et al note in their study that patient self-reported pain assessment is considered the gold standard of assessment and is the most accurate measurement tool [15]. Self-assessment of pain can result in inaccuracy if the patient is influenced by changes in mood, sleep disturbances, or medications [17]. Nurses, on the other hand, may be sceptical of the patient's self-assessment of pain, as they create their own standards of what is acceptable and when and how patients should express their pain [17].…”
Section: Assessment and Self-assessment Of Painmentioning
confidence: 99%